The Beginning of the End: A Chromosomal Assembly of the New World Malaria Mosquito Ends with a Novel Telomere. Issue 10 (1st October 2020) - Compton, Austin; Liang, Jiangtao; Chen, Chujia; Lukyanchikova, Varvara; Qi, Yumin; Potters, Mark; Settlage, Robert; Miller, Dustin; Deschamps, Stéphane; Mao, Chunhong; Llaca, Victor; Sharakhov, Igor V; et al.
Abstract: Chromosome level assemblies are accumulating in various taxonomic groups including mosquitoes. However, even in the few reference-quality mosquito assemblies, a significant portion of the heterochromatic regions including telomeres remain unresolved. Here we produce a de novo assembly of the New World malaria mosquito, Anopheles albimanus by integrating Oxford Nanopore sequencing, Illumina, Hi-C and optical mapping. This 172.6 Mbps female assembly, which we call AalbS3, is obtained by scaffolding polished large contigs (contig N50 = 13.7 Mbps) into three chromosomes. All chromosome arms end with telomeric repeats, which is the first in mosquito assemblies and represents a significant step toward the completion of a genome assembly. These telomeres consist of tandem repeats of a novel 30-32 bp Telomeric Repeat Unit (TRU) and are confirmed by analyzing the termini of long reads and through both chromosomal in situ hybridization and a Bal 31 sensitivity assay. The AalbS3 assembly included previously uncharacterized centromeric and rDNA clusters and more than doubled the content of transposable elements and other repetitive sequences. This telomere-to-telomere assembly, although still containing gaps, represents a significant step toward resolving biologically important but previously hidden genomic components. The comparison of different scaffolding methods will also inform future efforts to obtain reference-quality genomes for other mosquito species.